Explorations of enabled cyborgs: navigating blurry boundaries with a taste for ambiguous aesthetics - Buchan, Miles Isaac Emiliano, author; Ryan, Ajean, advisor; Riep, Dave, committee member; Romagni, Domenica, committee member; Plastini, Johnny, committee member (Colorado State University. Libraries, 2026)
This thesis proposes a personal philosophy and embodied practice grounded in the theory of "Ambiguous Aesthetics of Enabled Cyborgs". This practice uses drawing to map reality through the lens of lived experience with legal blindness and light sensitivity, generating visual evidence as it navigates both literal and conceptual spaces. The work examines the power of perception and the complexity of human ability through aesthetically ambiguous compositions that mobilize the unknown. These compositions prompt viewers to question their own search for meaning by introducing uncertainty. Through constraint and indeterminacy, ambiguity becomes a mechanism for experiencing perceptual loss, channeling both the sublime and the uncanny. This positions drawing as an ongoing investigative practice that explores the nature of reality and consciousness. It interrogates the processes that construct knowledge and acknowledges the fundamental uncertainty inherent in the formation of reality. Central to this research is the indeterminate nature of reality and its potential for change. Ultimately, the thesis advocates for empowering human abilities to improve the quality of life and includes diverse and marginalized ways of perceiving the world by promoting creative expression, intuitive understanding, and aesthetic experience.
Keywords: disability and art; embodied cognition; aesthetic ambiguity; perceptual loss; drawing as research